2015
DOI: 10.15740/has/as/10.1and2/30-34
|View full text |Cite
|
Sign up to set email alerts
|

Impact of mobile phone radiations on public health

Abstract: Mobile or cellular phones are now an integral part of modern telecommunications, the use of phones is not limited to phone calls only but people are getting various information's and using them for political, civic, health and many more purposes. In many countries, over half the population uses mobile phones. In 2014, there is an estimated 6.9 billion subscriptions globally and this number is going to rise sharply in coming years. In some parts of the world, mobile phones are the most reliable or the only phon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Studies have shown that these effects were associated with changes in distribution of ions [3]. According to some authors, there is connection with electromagnetic fields and disappearance of bees known as colony collapse disorder in Europe and the US, and that it could also interfere with bird migration [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that these effects were associated with changes in distribution of ions [3]. According to some authors, there is connection with electromagnetic fields and disappearance of bees known as colony collapse disorder in Europe and the US, and that it could also interfere with bird migration [4].…”
Section: Introductionmentioning
confidence: 99%